The Analysis of Optimal Portfolio Using Single Index Model, The Case of Stocks Listed In Jakarta Islamic Index 2010-2013 - Doddi Prastuti; Erti Septina (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
The purpose of this study is to apply the single index model in order to make an optimal portfolio for stocks listed in Jakarta Islamic Index (JII). The model is used in order to analyze what stocks to be chosen as components of a portfolio stock and how much proportion to be invested in each stock. This research use stocks that are listed in Jakarta Islamic Index. The reason for choosing stocks listed in JII is because many Indonesians, mostly Muslims, still not familiar with the stock that is accordance with the requirement of Sharia. The data use in this study is secondary data, among others: quarterly stock price data during period of 2010-2013, composite index, interest rate. Sample in this study are 28 companies’ stocks listed in the Jakarta Islamic Index, two companies’ stock did not meet the criteria of the sample because the companies start listed in the index in 2012. Data analysis methods use in this study are: stocks’ return and expected return, stocks’ risk, market’s return and risk, beta and alpha, variance of residual error, rate of excess return to beta, determine the cut off rate, proportion of fund invested in optimal portfolio, and risk of optimal portfolio. Result of this study showed that there are 10 stocks that meet the criteria of optimal portfolio formation. Those stocks and their proportion are: 24,852% stock of JMSR, 16,587% stock of ASRI, 14,721% stock of INDF, 15,398% stock of AKRA, 11,835% stock of LPKR, 5,684% EXCL, 5,184% MAPI, 3,143% CPIN, 1,511% SMGR and 1,086% stock of KLBF. Based on the calculation, the portfolio’s expected return is 10,33% and the risk is 2,74%.